2006
DOI: 10.1603/0022-2585(2006)43[731:rooole]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Repellency of Oils of Lemon Eucalyptus, Geranium, and Lavender and the Mosquito Repellent MyggA Natural to <I>Ixodes ricinus</I> (Acari: Ixodidae) in the Laboratory and Field

Abstract: MyggA Natural (Bioglan, Lund, Sweden) is a commercially available repellent against blood-feeding arthropods. It contains 30% of lemon-scented eucalyptus, Corymbia citriodora (Hook.) K. D. Hill & L. A. S. Johnson (Myrtaceae), oil with a minimum of 50% p-menthane-3,8-diol. MyggA Natural also contains small amounts of the essential oils of lavender, Lavandula angustifolia Mill. (Lamiaceae), and geranium, Pelargonium graveolens L'Her. (Geraniaceae). In laboratory bioassays, MyggA Natural and C. citriodora oil exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…These results conform to those of a previous study in which MyggA Natural (roll-on) was tested in the laboratory and field (Jaenson et al 2006). In that study we showed that the formulation compound, 1, 2-propanediol, of MyggA Natural does not repel I. ricinus nymphs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results conform to those of a previous study in which MyggA Natural (roll-on) was tested in the laboratory and field (Jaenson et al 2006). In that study we showed that the formulation compound, 1, 2-propanediol, of MyggA Natural does not repel I. ricinus nymphs.…”
Section: Discussionsupporting
confidence: 92%
“…A recently developed product, MyggA Ò Natural is based purely on naturally occurring plant compounds and contains as the main active substance para-menthane-3,8-diol (PMD) from the lemon eucalyptus Corymbia citriodora and small amount of terpene-fractions of essential oils of four different plant species. In a previous study MyggA Ò Natural (roll on) was shown to effectively repel ticks in Sweden (Jaenson et al 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Moore et al (2007) demonstrated efficacy of low-cost repellent containing PMD and lemongrass oil (with fixatives) for up to 6 h, which was more effective than DEET, against Anopheles darlingi in Peru. However, prolonged protection effects have been reported from 20% of the oil from turmeric, citronella, and hairy basil, especially with the addition of 5% vanillin as fixative in which they each can repel three species of mosquitoes for up to 6 h (Jaenson et al 2006). Seyoum et al (2002a) studied the repellency of live potted plants against Anopheles gambiae from human baits in semi-field experimental huts.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports on the insect repellency from mint (Teucrium leucocladum), citronella (Cymbopogon nardus), basil (Ocimum genus and their cultivars), thyme (Thymus vulgaris L.), neem (Azadirachta indica A. Juss), and lemongrass (Cymbopogon citratus; 9-14). Trongtokit et al have assessed repellent activity of 38 Thai essential oils and found that an effective time of repellency strongly depended on the concentrations, experiment designs, and mosquito species (14). It is obvious that repellent effects of natural oil are mostly shorter than the synthetic one like DEET.…”
Section: Introductionmentioning
confidence: 99%